Evaluation of Dry Eye After Refractive Surgery According to Preoperative Meibomian Gland Status - Gong, Qianwen; Li, Anqi; Chen, Lin; Chen, Huijuan; Gu, Jinjing; Xu, Zhiqiang; Lu, Fan; Hu, Liang (Frontiers in Medicine, 2022)
Purpose: To investigate the effect of the preoperative meibomian gland (MG) status on dry eye symptoms after corneal refractive surgery. Methods: This is a prospective, observational study. Subjects were enrolled and classified into 3 groups according to their MG loss grades. Ocular surface parameters were measured preoperatively and at 1 month, 3 months, and 6 months, postoperatively, including the ocular surface disease index questionnaire (OSDI), non-invasive tear film break up time (NITBUT), tear meniscus height and Schirmer I test. All the parameters were analyzed among the three groups, and different time points. Results: Seventy-eight patients were included in this study. The grade of MG loss varied from 0 to 2, thus the subjects were divided into group 1 to 3 corresponding to the MG loss. There were no significant differences in all parameters at baseline. The OSDI score increased in all groups at 1 month postoperatively and then decreased after other follow-ups. The OSDI was higher in group 3 than group 1 at all time points postoperatively (P=0.005, 0.002, 0.034). Besides, it was higher in group 2 at 3 months and 6 months, compared with group 1 (P=0.006, 0.029). The average NIBUT was shorter in group 3, compared with group 1 and group 2 since 1 month after surgery. At 1 month and 3 month postoperatively, the grade of MG loss was positively correlated with the total OSDI and the vision-related scores. And it showed a positive correlation only with the environmental score at 6 months postoperatively. Conclusions: The dry eye discomfortable symptoms significantly differed postoperatively according to their preoperative MG loss grade, though no difference was found at baseline. Dry eye was associated more with vision-related discomfort at first and environmental factors later.